2003
DOI: 10.1111/j.0952-1895.2004.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

How Democratic Is “Governance”? Lessons from Swiss Drug Policy

Abstract: Public action increasingly takes place in self-organizing networks that are remote from direct governmental control. While these transformations have been subject to scrutiny in regard to their efficiency, less attention has been paid to their democratic quality. This article discusses governance-induced problems of democracy by isolating two major criticisms. Deliberative criticism argues that governance, rather than allowing for true deliberation in the public space, may lead to a loss of accountability. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 27 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…Case studies of drug policy, public transport, cultural policy, and water provision have shown that lines of accountability are blurred in governance networks (Kübler & Schwab, 2007). The budgetary process seems to provide the main link for connecting governance networks to both elected politicians in representative institutions as well as the electorate through direct democratic instruments (Wälti, Kübler, & Papadopoulos, 2004). Legal procedures for budget or credit approval generally stipulate a cascade of decisions by different bodies (the executive, parliament, electorate) according to the amount that is involved.…”
Section: The Power Of Elected Politicians In Governance Networkmentioning
confidence: 99%
“…Case studies of drug policy, public transport, cultural policy, and water provision have shown that lines of accountability are blurred in governance networks (Kübler & Schwab, 2007). The budgetary process seems to provide the main link for connecting governance networks to both elected politicians in representative institutions as well as the electorate through direct democratic instruments (Wälti, Kübler, & Papadopoulos, 2004). Legal procedures for budget or credit approval generally stipulate a cascade of decisions by different bodies (the executive, parliament, electorate) according to the amount that is involved.…”
Section: The Power Of Elected Politicians In Governance Networkmentioning
confidence: 99%
“…This is an important component of the contribution of participatory tools to policy efficiency, but not the only one. In fragmented societies, ordinary majoritarian procedures can result in choices made by ill-informed majorities, causing prejudice to minorities whose intense preferences are thus violated (Guggenberger 1984;Scharpf 1999) -for instance, socially stigmatised groups (Waelti et al 2004). Moreover, as suggested by the literature on neo-corporatism considered as a governability device, electoral competition can engender over-promising and short-term calculations are innonative procedures in policy making democratic and effective?…”
Section: Efficiency and Effectivenessmentioning
confidence: 99%
“…These forms continue to provide the main basis for legitimate agency in the context of urban governance (Häikiö 2007). It seems that traditional routines of legitimization ensure that governance practices do not call into question representative institutions (Wälti et al 2004). The idea of representation and elected representatives representing collective interests (or the common good) justifies representative democracy as the main field of decision making in the context of the purchaser-provider model as well.…”
Section: Diverse Local Democracymentioning
confidence: 99%